Cultivating Critical Thinkers: Independent Curriculum Strategies to Enhance Critical Thinking Skills in Elementary Students - Rachmawati, Nur Hesti; Muhroji, Muhroji; Misyanto, Misyanto; Yusrin, Yusrin (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Perguruan Tinggi Muhammadiyah Aisyiyah, 2024)
Students are required to have critical thinking skills in order to be able to implement their knowledge. However, in reality, many students still have low critical thinking skills. Many students are less enthusias-tic about asking, answering, and expressing their opinions. This research aims to describe strategies for building critical thinking skills in elementary school students through an independent curriculum. This type of research is qualitative with a descriptive design. Data collection techniques include interviews, observation, and documentation. Data analysis uses interactive analysis techniques with three stages: data reduction, data presentation, and drawing conclusions. The results of the research are: the principal's strat-egy for improving students' critical thinking skills by implementing extracurricular activities. Class teach-ers, by implementing differentiated learning, implement projects to strengthen the profile of Pancasila and literacy students. As well as campus students, by implementing morning numeracy, morning literacy and additional classes for students who need intensive assistance. After implementing these various strategies, students' critical thinking abilities can improve, and even their' character can improve.